Ellipsometric and X‐Ray Spectrometric Investigation of Fibrinogen Protein Layers. Issue 12 (6th December 2017) - Kalas, Benjamin; Pollakowski, Beatrix; Nutsch, Andreas; Streeck, Cornelia; Nador, Judit; Fried, Miklós; Beckhoff, Burkhard; Petrik, Péter
Abstract : Bovine fibrinogen monolayers on thin gold films and glassy carbon substrate were investigated using grazing incidence X‐ray fluorescence (GIXRF) and spectroscopic ellipsometry (SE). The aim was to determine the amount of protein and to develop models and references for the SE measurement. Both methods were capable of measuring protein amount in the range of μg cm −2 with a sensitivity below 10%, which suggests the use of both techniques as complementary, combined methods. To do it with a high confidence, the lateral uniformity and the stability of the layers during transportation has to be investigated in more detail in the future. Abstract : Spectroscopic ellipsometry (SE) and X‐ray fluorescence (XRF) are used to measure protein monolayers on gold and amorphous carbon substrates. The amount of protein on the surface is quantified in terms of mass per unit area using de Feijter's method and a reference‐free approach for SE and XRF, respectively. A good agreement is found, pointing out the importance of the lateral homogeneity and temporal stability.